2020
DOI: 10.4102/jamba.v12i1.927
|View full text |Cite
|
Sign up to set email alerts
|

Collaborating network in managing post the Mount Merapi’s disruption, Indonesia

Abstract: Collaborative governance and social capital can help to form a resilient community in the wake of a disaster, such as the eruptions of Mount Merapi in Indonesia. This study examines the successfulness of the handling of disasters in Indonesia, with particular focus on eruptions of Mount Merapi. Disasters foster a close relationship between the government and the community in response to the emergency. This study uses a mixed method to analyse social networks in evaluating the structure of disaster networks in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…However, the result showed that governance significantly affects the motivation that arises in the initial agreement, expands trust, and increases network reliability and expertise (Pratama & Nurmandi, 2020).…”
Section: Managementmentioning
confidence: 97%
See 1 more Smart Citation
“…However, the result showed that governance significantly affects the motivation that arises in the initial agreement, expands trust, and increases network reliability and expertise (Pratama & Nurmandi, 2020).…”
Section: Managementmentioning
confidence: 97%
“…The high role of governance is shown in the study of Pratama and Nurmandi (2020) regarding the collaboration networks in dealing with the post-disaster eruption of Mount Merapi. The study explained that failure in the coordination process was caused by poor communication, misdirected and poorly executed leadership, inadequate coordination with stakeholders, as well as inadequate preparation among communities.…”
Section: Managementmentioning
confidence: 99%
“…This phase implies proactive approaches involving the identification of potential hazards and the formulation of precautionary measures to mitigate their impact. During this phase, the role of trust in risk management is paramount, with its efficacy depending on various factors, including leadership style and effective communication by authorities [38,39].…”
Section: Trust In the Prevention Phasementioning
confidence: 99%
“…Another study conducted by Pratama and Nurmandi [38] placed the focus on the importance of leadership in disaster prevention. The authors observed that the leadership style of institutions is significantly linked to the motivation for agreement about preventative actions in the community, thereby influencing community trust in the initial management of disasters.…”
Section: Trust In the Prevention Phasementioning
confidence: 99%
“…Extensive research over the years has demonstrated that disaster response is a complex process involving extensive networks of diverse public, private, and nonprofit organizations. These networks can consist of numerous nonprofit entities, often numbering in the thousands, that play a crucial role in providing essential resources, including leadership, during disaster responses (Alam and Ray-Bennett, 2021;Pratama and Nurmandi, 2020;Trainor and Velotti, 2013). Leaders in the regions, especially regional heads, need to conduct socialization on earthquake disasters which can be carried out with the following activities (Zakaria et al, 2011): 1) Counseling to the community using the PRA (Participation Rural Appraisal) method by involving rural communities so they can participate.…”
Section: Leadership In Disaster Governancementioning
confidence: 99%